PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE BERBANTUAN MEDIA POSTER DIGITAL TERHADAP KETERAMPILAN BERBICARA DAN MENULIS TEKS EKSPLANASI SISWA SEKOLAH DASAR - Wulandari, Anggun Tri; Azis, St Aida; Rimang, Sitti Suwadah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aimed to finding out whether there is an influence of the Think Talk Write learning model assisted by digital poster media on speaking and writing explanatory text skills. The type of research used is Quasi Experimental Design with the Nonequivalent Control Group Design type. The population in this study were all class VI students of Cluster III, Galesong District, which consists of six schools with a total number of students of 332. The sample in this study was class VI students of UPT SD Negeri 70 Boddia, totaling 53 people using cluster random sampling techniques. The data collection technique in this research was carried out through technical tests to determine speaking and writing skills in explanatory texts in the form of questions and reading texts. The research results are based on Independent Sample T Test Hypothesis 1, the basis for decision making, if the significance value is smaller than 0.05 then it can be stated that there is an influence of the Think Talk Write learning model assisted by digital poster media on speaking skills. The significance value obtained from the independent sample t test is 0.00, which is smaller than 0.05. Therefore, it can be stated that there is an influence of the Think Talk Write learning model assisted by digital poster media on speaking skills. Meanwhile, for the Independent Sample T Test Hypothesis 2 test results, the significance value obtained from the independent sample t test is 0.00, which is smaller than 0.05. Therefore, it can be stated that there is an influence of the Think Talk Write learning model assisted by digital poster media on explanatory text writing skills. And the results of the Manova test, the significance value obtained from the Manova test is 0.00, which is smaller than 0.05. Therefore, it can be stated that there is an influence of the Think Talk Write learning model assisted by digital poster media on speaking and writing explanatory text skills. Keywords: speaking skills, think talk write learning model, writing explanatory text